Coronary Artery Vessel Healing Pattern, Short and Long Term, After Implantation of the Everolimus‐Eluting Bioresorbable Vascular Scaffold. Issue 11 (November 2015) - Kraak, Robin P.; de Boer, Hans H.; Elias, Joëlle; Ambarus, Carmen A.; van der Wal, Allard C.; de Winter, Robbert J.; Wykrzykowska, Joanna J.
Abstract : Background: Although the Absorb bioresorbable vascular scaffold is increasingly used in daily clinical practice for the treatment of coronary artery disease, the exact vascular healing pattern and the resorption process in humans is unknown because histological data are derived only from animal studies. Methods and Results: We have obtained 4 autopsies (5 scaffolds) since August 2013. Duration of bioresorbable vascular scaffold implantation ranged from 3 to 501 days. All autopsies and histological assessments were performed by dedicated cardiovascular pathologists. At 1 week after bioresorbable vascular scaffold implantation, struts were covered with a fine layer of fibrin and platelets. At 113 days, the scaffold struts were fully covered with smooth muscle cells. Hyaline eosinophilic and proteoglycan material infiltrating the scaffold struts was observed at 501 days after implantation. At all time points, we observed the presence of multinuclear foreign body giant cells adjacent to the scaffold struts. Conclusions: Resorption and healing processes after bioresorbable vascular scaffold implantation in human patients mirror those observed in porcine models. The presence of multinucleated foreign body giant cells at both short‐ and long‐term follow‐up needs further investigation and may be related to a low‐grade absorptive inflammatory response to the polymer.